2022
DOI: 10.37896/ymer21.08/51
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Drought Tolerance of Medicinally Important Oil Yielding Plant Simarouba glauca

Abstract: The population growth also leads to the agricultural and industrial expansions. This adds to the various greenhouse gases leading to the unpredictable climatic change and global warming. The climate of region becomes uncertain, creating several abiotic stresses. It is essential to screen the perennial plant species to develop greenery so to minimize or overcome these adverse conditions. The Simarouba glauca is one of such hardy, evergreen edible oil trees, growing on waste lands. Keyword- Drought Tolerance, Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Positive results on osmoprotectant accumulation have been widely described in stressed plants of the genus Stipa (Yang et al, 2021). In the same direction, other results showed that ASA or ammonium sulphate increase proline concentration, flavonoids and phenolic compounds in Poaceae, such as Festuca arundinacea (Neuberg et al 2010) or in dicots such as Simarouba glauca (Awate et al, 2014) and chickpea (Hussain et al, 2020).…”
Section: Osmoprotectants and Non-enzymatic Antioxidantsmentioning
confidence: 71%
“…Positive results on osmoprotectant accumulation have been widely described in stressed plants of the genus Stipa (Yang et al, 2021). In the same direction, other results showed that ASA or ammonium sulphate increase proline concentration, flavonoids and phenolic compounds in Poaceae, such as Festuca arundinacea (Neuberg et al 2010) or in dicots such as Simarouba glauca (Awate et al, 2014) and chickpea (Hussain et al, 2020).…”
Section: Osmoprotectants and Non-enzymatic Antioxidantsmentioning
confidence: 71%